2021
DOI: 10.1093/aesa/saaa047
|View full text |Cite
|
Sign up to set email alerts
|

Interactions Among Native and Non-Native Predatory Coccinellidae Influence Biological Control and Biodiversity

Abstract: Over the past 30 yr, multiple species of predatory Coccinellidae, prominently Coccinella septempunctata L. and Harmonia axyridis (Pallas) (Coleoptera: Coccinellidae) have spread to new continents, influencing biodiversity and biological control. Here we review the mechanisms underlying these ecological interactions, focusing on multi-year field studies of native and non-native coccinellids and those using molecular and quantitative ecological methods. Field data from Asia show that H. axyridis, C. septempuncta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 177 publications
(218 reference statements)
0
19
0
Order By: Relevance
“…2017, 2020; Li et al . 2021) or alter the dynamics of what we observed under controlled conditions. This is the first report to confirm these interactions between C. montrouzieri and T. notata ; hence, it is essential to review the possible success or failure for the biological control of mealybugs where both of these lady beetle species occur simultaneously.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…2017, 2020; Li et al . 2021) or alter the dynamics of what we observed under controlled conditions. This is the first report to confirm these interactions between C. montrouzieri and T. notata ; hence, it is essential to review the possible success or failure for the biological control of mealybugs where both of these lady beetle species occur simultaneously.…”
Section: Discussionmentioning
confidence: 64%
“…Other factors such as weather conditions, habitat size, food availability, presence of other natural enemies etc. may impose disadvantages on native species (Kindlmann et al 2017(Kindlmann et al , 2020Li et al 2021) or alter the dynamics of what we observed under controlled conditions. This is the first report to confirm these interactions between C. montrouzieri and T. notata; hence, it is essential to review the possible success or failure for the biological control of mealybugs where both of these lady beetle species occur simultaneously.…”
Section: Discussionmentioning
confidence: 91%
“…Following their establishment, alien lady beetles became the dominant species within many native communities (Alyokhin & Sewell, 2004; Harmon et al ., 2007; Bahlai et al ., 2015). Because of their dominance, direct and indirect competitive interactions with alien species are hypothesized as a driver of declines in native lady beetles (Pell et al ., 2008; Li et al ., 2021). For example, intraguild predation has been documented among native and alien lady beetles in the field (Gagnon et al ., 2011; Thomas et al ., 2013; Brown et al ., 2015; Ortiz-Martínez et al ., 2020), wherein native eggs and larvae were more likely to be the intraguild prey for alien species (Snyder et al ., 2004; Katsanis et al ., 2013).…”
Section: Introductionmentioning
confidence: 99%
“…For example, H. axyridis and C. septempunctata were highly abundant within native lady beetle communities that were sampled over 24 years in southwestern Michigan, USA (Bahlai, Colunga-Garcia, et al 2015). Because H. axyridis and C. septempunctata have become the dominant lady beetles within many native communities (Alyokhin and Sewell 2004, Harmon et al 2007, Bahlai, Colunga-Garcia, et al 2015), direct and indirect forms of competition are hypothesized as drivers of declines in native species (Pell et al 2008, Li et al 2021).…”
Section: Introductionmentioning
confidence: 99%